Platelet-rich fibrin improves repair and regeneration of damaged endometrium in rats - Mao, Lele; Wang, XiaoXue; Sun, Yu; Yang, Mukun; Chen, Xing; Cui, Lei; Bai, Wenpei (Frontiers in Endocrinology, 2023)
Purpose Intrauterine adhesion (IUA) is the most common cause of uterine infertility. This study aims to evaluate whether platelet-rich fibrin (PRF) treatment can stimulate damaged endometrium regeneration in rats. Methods First, hematoxylin and eosin (HE) staining, scanning and transmission electron microscopy, and ELISAs were used to evaluate the microstructure of PRF. Then, mechanical damage was used to establish an IUA rat model. A total of 40 SD female rats were randomized to three groups: PRF transplantation group, IUA group, and sham group. Rats were sacrificed at 3, 7, and 14 days and uteruses were obtained for further analysis. Finally, functional and histological recovery of the damaged endometrium was analyzed by pregnancy test, HE staining, Masson’s staining, and immunohistochemistry. Results PRF has two distinct zones, platelets and fibrin zone. Long and narrow fibrin fibers interconnected with each other and formed a three-dimensional, flexible, and elastic structure; platelet aggregates were trapped in fibrin fibers, and each platelet is associated with several fibrin fibers. PRF exudates promoted endometrial stromal cell proliferation and migration in vitro. PRF transplantation was beneficial for maintaining uterine structure, promoting endometrial luminal epithelium and endometrial gland regeneration, and decreasing fibrotic areas in vivo. Conclusion Intrauterine administration of PRF was demonstrated to be effective in preventing IUA and stimulating damaged endometrium regeneration in rats. This study not only provided a promising method for its potential in endometrial regeneration in women who suffer from uterine infertility but also may prevent IUA after intrauterine surgery in clinical cases.